Study on direct-contact phase-change liquid immersion cooling dense-array solar cells under high concentration ratios. (15th November 2016) - Kang, Xue; Wang, Yiping; Huang, Qunwu; Cui, Yong; Shi, Xusheng; Sun, Yong
Highlights: Direct-contact phase-change liquid immersion cooling for solar cells was proposed. A self-regulating system investigated the feasibility in temperature control. Temperature was well controlled between 87.3 °C and 88.5 °C. Surface heat transfer coefficient was up to 23.49 kW/(m 2 ·K) under 398.4×. A model illustrated the interface function was the main reason to affect light. Abstract: A new cooling method by directly immersing the solar cells into phase-change liquid was put forward to cool dense-array solar cells in high concentrating photovoltaic system. A self-running system was built to study the feasibility of temperature control and the effect of bubbles generated by ethanol phase change under concentration ratio ranged between 219.8× and 398.4×. The results show that the cooling system is self-regulating without consuming extra energy and ethanol flow rate reaches up to 180.6 kg/(s·m 2 ) under 398.4×. The temperature of solar cells distributes in the range between 87.3 °C and 88.5 °C, the surface heat transfer coefficient of electric heating plate is up to 23.49 kW/(m 2 ·K) under 398.4×. The bubble effect on electrical performance of triple-junction solar cells is reported and the results show that Isc and P max decline 10.2% and 7.3%, respectively. A model based on bubble images illustrates that light loss at the interface between ethanol and bubble is the main reason to cut down the electrical performance.